2018
DOI: 10.1111/1759-7714.12623
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA linc01433 promotes migration and invasion in non‐small cell lung cancer

Abstract: BackgroundFor many years, lung cancer has been the most common and deadly cancer worldwide. Early diagnosis of non‐small cell lung cancer (NSCLC) in particular is very difficult because the symptoms are often ignored. The five‐year survival rate is very low despite great improvements to therapy. Thus, there is an urgent need to identify prognostic biomarkers and target molecules for the clinical diagnosis and individualized treatment of NSCLC.MethodsWe performed quantitative real‐time PCR to determine the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 49 publications
2
16
2
Order By: Relevance
“…A recent study has reported over-expression of LINC01433 in NSCLC samples compared with the normal non-tumoral tissues. Their in vitro experiments also verified the results of the previous study regarding the oncogenic role of this lncRNA [8]. Based on these studies, we aimed to confirm these results in Iranian NSCLC patients.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…A recent study has reported over-expression of LINC01433 in NSCLC samples compared with the normal non-tumoral tissues. Their in vitro experiments also verified the results of the previous study regarding the oncogenic role of this lncRNA [8]. Based on these studies, we aimed to confirm these results in Iranian NSCLC patients.…”
Section: Introductionsupporting
confidence: 82%
“…There was no significant difference in the expression of LINC01433 between tumoral and non-tumoral tissues (expression ratio 0.67, p = 0.42). Expression of this lncRNA was not associated with any [8], which was not revealed in our study. In brief, our study did not verify the overexpression of LINC01433 in NSCLC Iranian patients despite the reported oncogenic role of this lncRNA.…”
Section: Expression Assaycontrasting
confidence: 77%
See 1 more Smart Citation
“…Various studies have suggested that the dysregulation of lncRNA is associated with lung cancer. Compared to normal lung tissue, linc01433 is significantly overexpressed and promotes migration and invasion in NSCLC . LINC00094 is highly expressed in lung cancer tissues and could be a molecular target for therapy for smoking‐related lung cancer .…”
Section: Long Non‐coding Rnas (Lncrnas) and Non‐small Cell Lung Cancementioning
confidence: 99%
“…Compared to normal lung tissue, linc01433 is significantly overexpressed and promotes migration and invasion in NSCLC. 13 LINC00094 is highly expressed in lung cancer tissues and could be a molecular target for therapy for smoking-related lung cancer. 14 In recent years, emerging evidence has confirmed the role of lncRNAs in drug resistance.…”
Section: Introductionmentioning
confidence: 99%